Effective coverage for maternal health: Operationalising effective coverage cascades for antenatal care and nutrition interventions for pregnant women in seven low- and middle-income countries - Sheffel, Ashley; Carter, Emily; Heidkamp, Rebecca; Hossain, Aniqa Tasnim; Katz, Joanne; Kim, Sunny S.; Lama, Tsering Pema; Marchant, Tanya; Perin, Jamie; Requejo, Jennifer; Walton, Shelley; Munos, Melinda K. (International Society of Global Health, 2025)
Background Efforts to improve maternal health have focused on measuring health and nutrition service coverage. Despite improvements in service coverage, maternal mortality rates remain high. This suggests that coverage indicators alone do not fully capture the quality of care and may overestimate the health benefits of a service. Effective coverage (EC) cascades have been proposed as an approach to capture service quality within population-based coverage measures, but the proposed maternal health EC cascades have not been operationalised. This study aims to operationalise the effective coverage cascades for antenatal care (ANC) and maternal nutrition services using existing data from low- and middle-income countries (LMICs).